أثر الزحام على بعض مناسك الحج: دراسة فقهية مقارنة - محمد، فاطمة المتولي عبده (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بالمنصورة, 2022)
الحج هو ركن من أركان الإسلام ولكنه قيد بمن استطاع إليه سبيلا ومع شوق المسلمين لأداء الفريضة وزيارة الكعبة المشرفة، ولقدسية هذه الأماكن والروحانيات بها يحرص المسلمون على أداء النسك، ويترتب على هذا حدوث زحام في أداء المناسك، وقد تناولت أسباب الزحام من الناحية العمرانية، وطبيعة الأماكن، ومن حيث سلوكيات الأفراد، وتناولت ما يترتب على هذا الزحام من التأثير على مناسك الحج، ومتى يسقط عنه الأداء، وعرض الحلول التي تمت بالفعل للتخفيف من شدة الزحام، والحلول المقترحة، وإبراز أراء الفقهاء، واختلافهم في بعض المناسك، واختيار ما يتناسب وتغير الحال، وبيان مرونة الشريعة الإسلامية وصلاحيتها لكل زمان ومكان. وقد اقتضت طبيعة البحث أن أقسمه إلى مقدمة، وستة مباحث؛ أما المقدمة فقد اشتملت على أهمية الموضوع، وأسباب اختياري للموضوع، ومنهجي في البحث، وأما المبحث الأول ففي التعريف بمصطلحات البحث، وأسباب الزحام، وحلوله، وأما المبحث الثاني ففي أثر الزحام على وجوب الحج، وأما المبحث الثالث ففي أثر الزحام على الطواف، وأما المبحث الرابع ففي أثر الزحام على السعي، وأما المبحث الخامس ففي أثر الزحام على الوقوف بعرفة والمبيت بمزدلفة، وأما المبحث السادس ففي أثر الزحام على المبيت بمنى، وأما الخاتمة فقد اشتملت على أهم نتائج البحث وتوصياته. Hajj is one of the pillars of Islam, but it is a restriction on those who are able to do so. With the desire of Muslims to perform the obligatory duty and visit the Kaaba, and for the sanctity of these places and spirituality, Muslims are keen to perform rituals, and this results in crowding in performing the rituals. The places, and in terms of the behavior of individuals, and dealt with the consequences of this crowding of the impact on the rituals of Hajj, and when the performance drops from it, and presented the solutions that have already been made to reduce the severity of the crowding, and the proposed solutions, and highlight the opinions of scholars, and their differences in some of the rituals, and choose what suits the change of situation, And a statement of the flexibility of Islamic law and its validity for every time and place. The nature of the research necessitated that I divide it into an introduction and six chapters. As for the introduction, it included the importance of the topic, the reasons for my choice of the topic, and the methodology of the research. The first topic deals with the definition of the search terms, causes of crowding, and its solutions. As for the second topic, it deals with the effect of crowding on the necessity of Hajj. As for the third topic, it deals with the impact of crowding on circumambulation. The fourth topic deals with the effect of crowding on the quest, and the fifth topic deals with the impact of crowding on stopping in Arafat and staying overnight in Muzdalifah, and as for the sixth topic, it deals with the impact of crowding on staying overnight in Mina, and the conclusion included the most important results and recommendations of the research.
Keywords: مناسك الحج -- الفقه الإسلامي -- الدراسات الإسلامية -- الشريعة الإسلامية